(untitled) - Schmitt, Conrad J. (New York, 1998)
Activities Workbook and Student Tape Manual SE: Both components are in one volume. Workbook contains many activities in "game" formats. Tape Manual contains "Listen and repeat," "Listen and answer," and "Listen and choose" activities.
Keywords: Standard usage (prescriptive linguistics),Applied linguistics,Foreign language